Anti-Hyperuricemic and Nephroprotective Effects of Dihydroberberine in Potassium Oxonate- and Hypoxanthine-Induced Hyperuricemic Mice - Xu, Lieqiang; Lin, Guoshu; Yu, Qiuxia; Li, Qiaoping; Mai, Liting; Cheng, Juanjuan; Xie, Jianhui; Liu, Yuhong; Su, Ziren; Li, Yucui (Frontiers in Pharmacology, 2021)
Phellodendri Chinese Cortex has long been used to treat hyperuricemia and gout. Berberine (BBR), as its characteristic ingredient, has also been shown to be effective in alleviating monosodium urate crystals-triggered gout inflammation in vitro and in vivo. Dihydroberberine (DHB) is a hydrogenated derivative of BBR that shown improved in vivo efficacy on many metabolic disorders. However, its anti-hyperuricemia effect remains underexplored. In the present work, the hypouricemic and renoprotective effects of DHB on hyperuricemic mice was investigated. The hyperuricemic mouse model was induced by intraperitoneal injection of potassium oxonate (PO, 300 mg/kg) combined with intragastric administration of hypoxanthine (HX, 300 mg/kg) for 7 days. Different dosages of DHB (25, 50 mg/kg), BBR (50 mg/kg) or febuxostat (Feb, 5 mg/kg) were orally given to mice one hour after modeling. The molecular docking results showed that DHB effectively inhibited xanthine oxidase (XOD) by binding with its active site. In vitro, DHB exhibited significantly XOD inhibitory activity (IC50 value, 34.37 μM). The in vivo results showed that DHB has obvious hypouricemic and renoprotective effects in hyperuricemic mice. It could not only lower the uric acid and XOD levels in serum, but also suppress the activities of XOD and adenosine deaminase (ADA) in the liver. Furthermore, it could noticeably down-regulate the renal mRNA and protein expression of XOD. Besides, DHB remarkably and dose-dependently ameliorated renal damage, which was proved by considerably reduced serum creatinine and blood urea nitrogen (BUN) levels, inflammatory cytokines (TNF-α, IL-1β, IL-6 and IL-18) levels and restored kidney histological changes. Further mechanistic investigation showed that DHB distinctly down-regulated renal mRNA and protein levels of URAT1, GLUT9, NOD-like receptor 3 (NLRP3), apoptosis-associated speck-like (ASC), caspase-1 and IL-1β. Our study revealed that DHB had outstanding hypouricemic and renoprotective effects via suppressing XOD, URAT1, GLUT9 and NLRP3 inflammasome activation in the kidney.